¿Quién raya la cancha? : visiones, tensiones y nuevas perspectivas en los estudios socioculturales del deporte en Latinoamérica - Fernández Vergara, Omar (Free online access: CLACSO., 2017)
The book you have in your hands is the result of collective effort and dreams that articulately manage to materialize in a publication that is offered to Latin America and the world. It is the result of the transformation of dreams into projects and the struggle involved in materializing them in society. It is the work of various professionals in the social sciences, who today more than professionals, we can call many fellow travelers, and friends of life. For this reason, this publication that arises from Chile is a gift for those minds that seek guidance regarding the Social Studies of Sport in our continent. It is a present for all of our colleagues who in Latin America are making it possible for sport to be a tool for social transformation.